Centering Disability Perspectives in Algorithmic Fairness, Accountability, and Transparency - Givens, Alexandra Reeve; Morris, Meredith Ringel (FAT* 2020, 2020)
The associated PDF download contains the extended abstract describing our FAT* 2020 CRAFT Panel on Centering Disability Perspectives in Algorithmic Fairness, Accountability, and Transparency. The panel discussion takes place on January 30, 2020 as part of the FAT* conference's CRAFT program.